Single- and Multi-Element Quantification and Characterization of TiO2 Nanoparticles Released From Outdoor Stains and Paints - Azimzada, Agil; Farner, Jeffrey M.; Jreije, Ibrahim; Hadioui, Madjid; Liu-Kang, Carolyn; Tufenkji, Nathalie; Shaw, Phil; Wilkinson, Kevin J. (Frontiers in Environmental Science, 2020)
With growing applications of TiO2 nanoparticles (NPs) in outdoor surface coatings, notably in paints and stains, their release into the environment is inevitable. This work measured NPs released from painted and stained surfaces and characterized them by size and composition using magnetic sector single particle inductively coupled plasma mass spectrometry (SP-ICP-MS) and SP-ICP-time-of-flight-MS (SP-ICP-TOF-MS). Two in situ experimental plans were examined in which natural precipitation interacted with nano-enhanced surfaces to varying degrees during the fall and winter. Weathering data showed that longer contact times of the precipitation (snow and rain) resulted in greater NP release. Although the stained surfaces had far fewer NPs per unit area, they lost a much higher fraction of their NP load (max 6% leached, as opposed to <10-4 % in paints), over similar exposure times. NP release was particularly enhanced for conditions of frequent rainfall and spring snow melt (i.e. slushy snow). SP-ICP-TOF-MS measurements on the Ti NPs indicated that they were often associated with a secondary metal in both the liquid paint (Al was detected in 20% of the Ti NPs; Zr in about 1% of the NP) and the liquid stain (Fe was detected in 7%, Si in 8% and Al in 3 % of the Ti NPs). In contrast, for the vast majority of Ti NPs being leached out of the painted/stained surfaces, only Ti was detected. Metal interactions in the paint were explained by binding of the TiO2 within a complex paint matrix; while in the stain, TiO2 NPs were hypothesized to be found in heteroagglomerates, potentially with aluminosilicates (Fe, Si and Al). In rain and snow, Ti was the only element detected in about half of the Ti NPs; in the other half, Ti often co-occurred with Fe, Si and Al. The results indicate that single element, likely anthropogenic, Ti NPs are already prevalent in the natural precipitation and that NP release from surface coatings will further increase their presence in the environment.